Cost-effectiveness of glass hybrid versus composite in a multi-country randomized trial. (April 2021) - Schwendicke, Falk; Rossi, Jesus Gomez; Krois, Joachim; Basso, Matteo; Peric, Tamara; Turkun, Lezize Sebnem; Miletić, Ivana
Abstract: Objectives: We assessed the cost-effectiveness of two amalgam alternatives, glass hybrid (GH) and composite (CO) in a multi-country randomized controlled split-mouth trial. Materials: University clinics in Croatia, Serbia, Italy and Turkey participated. Pairs of GH (EQUIA Forte, GC) and a nano-hybrid CO (TetricEvoCeram, IvoclarVivadent) were randomly placed in occlusal-proximal two-surfaced cavities in permanent molars of adults (n = 180/360 patients/molars). We used 3-years interim data for this evaluation. FDI-2 criteria were applied and teeth requiring repair, re-restoration, endodontic treatment or extraction recorded. Our outcome was the time until any or major complications (requiring endodontic treatment or extraction) occurred. Costs were calculated in US Dollar (USD) 2018, with the local currencies being converted using Purchasing Power Parities. To estimate initial and re-treatment costs, a payers' perspective was taken and direct medical costs estimated from fee item catalogues. Incremental-cost-effectiveness ratios (ICER) were used to express the cost difference per gained or lost effectiveness. Results: Overall costs were lower for GH than CO in Croatia, Turkey and Serbia, while this difference was minimal in Italy. GH tended to survive longer than CO in Croatia and Italy, and shorter in Serbia and Turkey; overall survival time was not significantly different (p = 0.67/log-rank). The cost-effectiveness differences indicated CO to be more expensive at limited (ICER: 268.5 USD/month without any complications) or no benefit at all (-186.2 USD/month without major complications). Conclusions: GH was less costly than CO both initially and over 3 years. Efficacy differences were extremely limited. Clinical significance: Given their low initial costs and as efficacy between GH and CO did not differ significantly, GH had a high chance of being more cost-effective within this specific trial.